2019
DOI: 10.1371/journal.pcbi.1006803
|View full text |Cite
|
Sign up to set email alerts
|

Improving the reliability of model-based decision-making estimates in the two-stage decision task with reaction-times and drift-diffusion modeling

Abstract: A well-established notion in cognitive neuroscience proposes that multiple brain systems contribute to choice behaviour. These include: (1) a model-free system that uses values cached from the outcome history of alternative actions, and (2) a model-based system that considers action outcomes and the transition structure of the environment. The widespread use of this distinction, across a range of applications, renders it important to index their distinct influences with high reliability. Here we consider the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
201
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(228 citation statements)
references
References 54 publications
25
201
2
Order By: Relevance
“…As a reference, we simulated correct model-based agents, based on the hybrid model proposed by Daw et al with w = 1. 7 Consistent with recent work by Sharar et al, 26 even when agents have a w equal to exactly 1, used the correct model of the task, and performed 1 000 trials, the recovered w parameters were not always precisely 1 ( Figure 2I). This is expected, because parameter recovery is noisy and in the standard specification of the hybrid model w cannot be greater than 1, thus any error was an underestimate of w.…”
Section: Model-based Learning Can Be Confused With Model-free Learningsupporting
confidence: 85%
“…As a reference, we simulated correct model-based agents, based on the hybrid model proposed by Daw et al with w = 1. 7 Consistent with recent work by Sharar et al, 26 even when agents have a w equal to exactly 1, used the correct model of the task, and performed 1 000 trials, the recovered w parameters were not always precisely 1 ( Figure 2I). This is expected, because parameter recovery is noisy and in the standard specification of the hybrid model w cannot be greater than 1, thus any error was an underestimate of w.…”
Section: Model-based Learning Can Be Confused With Model-free Learningsupporting
confidence: 85%
“…On half the trials, the SS reward was available immediately (now condition), whereas on the other half of the trials, the SS reward was available only after a 30d delay (not now condition). In the now condition, the SS reward consisted of $10 available immediately and LL rewards consisted of all combinations of fourteen reward amounts (10.1, 10.2, 10.5, 11,12,15,18,20,30,40,70, 100, 130, 150 dollars) and seven delays (1,3,5,8,14,30,60 days). Trials for the not now condition where identical, with the exception that an additional delay of 30 days was added to both options, such that in not now trials, the SS reward was always associated with a 30 day delay, and LL reward delays ranged from 31 to 91 days.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in perceptual decision-making, sequential sampling models such as the drift diffusion model (DDM) that not only account for the observed choices but also for the full reaction time distributions have a long tradition [8][9][10] . Recent work in reinforcement learning [11][12][13][14] intertemporal 15,16 and simple value-based choice [17][18][19][20] has shown that sequential sampling models can be successfully applied in these domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is compatible with a predominantly presynaptic effect of Haloperidol in the present study, leading to an overall increase in striatal dopaminergic signaling. Importantly, we extend previous pharmacological studies by applying a modeling framework for temporal discounting data that is based on a combination of standard discounting models with the drift diffusion model (DDM) 3033 , allowing us to comprehensively examine drug effects on RT components related to both valuation and non-valuation related processes.…”
Section: Introductionmentioning
confidence: 99%